2012
DOI: 10.3758/s13423-012-0286-y
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and modeling attentional dwell time

Abstract: Attentional dwell time (AD) defines our inability to perceive spatially separate events when they occur in rapid succession. In the standard AD paradigm, subjects should identify two target stimuli presented briefly at different peripheral locations with a varied stimulus onset asynchrony (SOA). The AD effect is seen as a long-lasting impediment in reporting the second target, culminating at SOAs of 200-500 ms. Here, we present the first quantitative computational model of the effect-a theory of temporal visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 50 publications
7
37
0
Order By: Relevance
“…A previous study suggests that sustaining an attentional set to perform a visual monitoring task and maintaining information in VSTM can interfere in some circumstances (Helton and Russell, 2013). This is compatible with the idea that activation-based maintenance in VSTM relies on neuronal resources necessary for encoding new visual information (Petersen et al, 2012; Schneider, 2013). The present results do not indicate such interference.…”
Section: Discussionsupporting
confidence: 87%
“…A previous study suggests that sustaining an attentional set to perform a visual monitoring task and maintaining information in VSTM can interfere in some circumstances (Helton and Russell, 2013). This is compatible with the idea that activation-based maintenance in VSTM relies on neuronal resources necessary for encoding new visual information (Petersen et al, 2012; Schneider, 2013). The present results do not indicate such interference.…”
Section: Discussionsupporting
confidence: 87%
“…The general framework of TVA, which will be presented below, has been highly successful in accounting for a wide range of findings within the attention literature (for an overview, see [2,3]). Until recently, however, few TVA-based studies had investigated attentional effects within the temporal domain [4][5][6][7]. Here, we substantially extend one of these previous studies [4] and present the first parametric investigation of the relationship between temporal expectations and the way in which we process information.…”
Section: Introductionmentioning
confidence: 67%
“…The VSTM system is conceived as a feedback mechanism that sustains activity in the neurons that have won the attentional competition, making the information represented by these neurons available for other cognitive processes. Recently, it has been suggested that this feedback mechanism may underlie the attentional dwell time phenomenon [5] (i.e. the inability to correctly identify the second of two targets presented in close temporal proximity).…”
Section: (D) Neural Interpretationmentioning
confidence: 99%
“…In this procedure, two masked target objects are presented, one after the other, and the time delay between the target presentations is manipulated. Subjects often find it difficult to perceive the second target when the delay between it and the previous target is short (generally between 200 and 500 ms; Duncan, Ward, & Shapiro, 1994; but see Petersen, Kyllingsbaek, & Bundesen, 2012;Theeuwes, Godijn, & Pratt, 2004). Selective attention is locked onto the first target for a period of time after that target is presented; targets presented before selective attention is released are less likely to be processed (Petersen et al, 2012).…”
Section: Attentional Dwell Timementioning
confidence: 99%